La programmation déterministe du budget de capital : un modèle financier - Chateau, Jean-Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractThe financial model presented in the article attempts to further integrate capital budgeting into the firm's overall financial planning policy. Although it is an extension and generalization of Bernhard and Weingartner's previous models, it differs from these works by some basic assumptions related to both the objective function and constraint set.First, the objective function stresses the growing role of managerial discretion as opposed to the common assumption of maximizing shareholders' wealth. In particular we assume that managers wish to maximize the size of the firm under their control at the end of some future time horizon. Since net cash flows of the investment projects selected are sources of future investment funds, the managers try to keep the shareholders' dividends to a minimum level, sufficient enough however to pacify them.Secondly, the model constraints embody the complete set of financial instruments available to the corporation managers: in a sense, this enlarges the previous models' short-term external financing facilities by considering simultaneously the alternative long-term external financial instruments, namely equity and bond issues. In the latter case, the refunding features are incorporated in the constraints. The constraints also imply that managers prefer steady growth of net cash flows through time. This contrasts with the usual maximization approach which has been shown to favor long-term investment projects with somewhat more erratic net cash flows.The derivation of the Kuhn and Tucker conditions for the model allows us to show the impact of the opportunity cost of the various instruments on that of the liquidity requirement and the investment projects selection criterion. Finally, the duality properties also highlight the reciprocal relationships existing between the various opportunity costs, both internal and external.